2020
DOI: 10.7150/ijms.47168
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of Gamma Knife Radiosurgery for Postsurgical residual or recurrent nonfunctioning Pituitary Adenomas

et al.

Abstract: Introduction: The aim of this retrospective study was to analyze the long-term outcomes and factors associated with treatment failure of Gamma Knife radiosurgery (GKRS) for postsurgical residual or recurrent nonfunctioning pituitary adenomas (NFPAs). Design and Methods: A total of 148 cases of postsurgical residual or recurrent NFPA patients were enrolled in the study. There were 111 cases with residual tumor and 37 cases with recurrent tumor. The median age was 46.0 years (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Study details, treatment overview and outcomes are reported in Table 1 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Across all 18 papers, the median number of patients treated in single institutional case series was 57 (range, 30–272 patients).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study details, treatment overview and outcomes are reported in Table 1 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Across all 18 papers, the median number of patients treated in single institutional case series was 57 (range, 30–272 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Random effects meta-analysis for five-year PFS are shown in Figure 2 b, with estimates of 95% (95% CI: 91–99%; I 2 = 0%, p = 1.00). Only six studies reported the 10-year PFS ranging 74–92% [ 11 , 12 , 17 , 18 , 19 ]. Notably, referring to tumor volume decrease after GK, the majority of studies reported a rate tumor shrinkage of at least 50% (range, 25–83%) over time.…”
Section: Resultsmentioning
confidence: 99%
“…Gamma Knife radiosurgery (GKRS) which has advantages of a highly precise, better dose conformity and focused delivery of radiation in a single session, is one of the best radiation technique and essential part in the treatment of pituitary tumors. As previous publications reported (4)(5)(6)(7)(8)(9)(10)(11)(12), GKRS has been proved to offer a high tumor control rate of 83-95% and a low new-onset hypopituitarism rate of 9-32% for pituitary adenomas. Treatment failure after GKRS for NFPAs consists of progressive cystic enlargement, tumor apoplexy and tumor regrowth (4).…”
Section: Introductionmentioning
confidence: 86%
“…4 SRS affords high tumor control rates, estimated to range between 89% and 91%. [5][6][7] Its popularity has emerged from the benefits of a minimally invasive approach, a modest risk profile, and the convenience of an outpatient procedure. 8 In SRS dose planning, achievement of tumor control with minimal treatment-related morbidity depends on the radiation dose delivered to the pituitary adenoma, the distance from the SRS target to critical hypothalamic-pituitary axis (HPA) neuroanatomic structures and the resultant SRS doses delivered along the HPA.…”
mentioning
confidence: 99%
“…4 SRS affords high tumor control rates, estimated to range between 89% and 91%. 5-7 Its popularity has emerged from the benefits of a minimally invasive approach, a modest risk profile, and the convenience of an outpatient procedure. 8…”
mentioning
confidence: 99%